The man behind the events: Human and political nature in classical historiography, by Antonio Hermosa Andújar (2019), Athenaica Ediciones Universitarias, 246 p. (2020)
What are we? With this question, the essay The man behind the events opens, Antonio Hermosa questioning himself and directly questioning the reader, who encourages them to reflect on the ethical-political bases from which coexistence or justice is organized, dissociating the question of any identity interpretation because what is at stake is to discover the ontoanthropological structure of sapiens from some decisive documents that emerged from the Western tradition.